2017
DOI: 10.1007/s00449-017-1879-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate removal in a combined bioelectrochemical and sulfur autotrophic denitrification system under high nitrate concentration: effects of pH

Abstract: A combined bioelectrochemical and sulfur autotrophic denitrification (CBSAD) system was established to treat high concentration nitrate under different pH conditions in this study. The microbial communities and structures were evaluated to deeply reveal the nitrate removal mechanisms in this combined system. When initial pH was adjusted to 6.5, the CBSAD system obtained 66.45% denitrification efficiency. The combined system achieved highest nitrate removal efficiency of 96.84% at pH 7.5. However, nitrate remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The SSS and SW reactors have better pH buffering performance, where scallop shells can provide a certain alkaline source for the reactor, highlighting the important role of scallop shells in stabilizing the pH of the reactor. 33 As shown in eqn (1), in the SAD process, some SO , combined with the results of the analysis in section 3.1.1, showed that the SW and SC reactors had poor denitrification performance, further indicating that no significant SAD process occurred in the SW and SC reactors. Notably, the SO 4 2− accumulation rate (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The SSS and SW reactors have better pH buffering performance, where scallop shells can provide a certain alkaline source for the reactor, highlighting the important role of scallop shells in stabilizing the pH of the reactor. 33 As shown in eqn (1), in the SAD process, some SO , combined with the results of the analysis in section 3.1.1, showed that the SW and SC reactors had poor denitrification performance, further indicating that no significant SAD process occurred in the SW and SC reactors. Notably, the SO 4 2− accumulation rate (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The SSS and SW reactors have better pH buffering performance, where scallop shells can provide a certain alkaline source for the reactor, highlighting the important role of scallop shells in stabilizing the pH of the reactor. 33…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria were found in denitrification systems in previous research [ 25 , 44 , 45 ], and showed good nitrate removal abilities and chromium reduction efficiency under neutral conditions for higher denitrification [ 46 ]. Proteobacteria and Firmicutes were found to be the dominant phyla in a laboratory-scale combined bioelectrochemical and sulfur autotrophic denitrification system and an expanded granular sludge bed reactor for the simultaneous biological removal of sulfate, nitrate, and lactate [ 47 , 48 ]. Proteobacteria contains many types of metabolic bacteria, and is responsible for the removal of COD and nitrogen, making Proteobacteria the most abundant phylum in sewage treatment and sulfur autotrophic denitrification processes [ 35 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Betaproteobacteria and Epsilonproteobacteria were the main denitrification bacteria in large sulfur/limestone autotrophic denitrification filters under low-temperature conditions [ 52 ]. Bacteroidia has been reported in a combined bioelectrochemical and sulfur autotrophic denitrification system, an anoxic–aerobic sequential batch reactor, and a mining clarifying pool [ 48 , 50 , 59 , 60 ], suggesting that some microorganisms in the Bacteroidia class might play a role in the denitrification process. Acidobacteria are a major microbial class in the phylum Acidobacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation